Peran Stakeholder Pada Perhitungan PDRB Sub-sektor Kehutanan di Provinsi Jawa Timur - Asihing Kustanti; Rizka Amalia; Tanjung Prameswari; Faridha Hanim (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Forests contribute as important capital in national development with various strategic functions in the ecological, economic, and socio-cultural fields. In East Java Province, forest area management not only aims to preserve the environment, but also to improve the welfare of the community around the forest through the sustainable use of forest products. This management involves various stakeholders, including the Forestry Service (DISHUT), Perum Perhutani, and other related agencies. Synergy between stakeholders is needed to optimize the contribution of the forestry sub-sector to regional development, especially in supporting the preparation of the Gross Regional Domestic Product (GDP) which reflects the real economic value of forest products. Therefore, mapping the roles between stakeholders is important in creating effective and sustainable forestry governance in East Java. This study aims to analyze the role of stakeholders in the calculation of the GDP of the forestry sub-sector in East Java Province. This research uses a mixed method. The data sources for this study came from 4 informants and 61 respondents. The analysis was carried out quantitatively-descriptively and qualitatively through interactive models and role analysis. The results show that each stakeholder has a diverse role in the calculation of the GDP of the forestry sub-sector. The Forestry Service and BAPPEDA are the main actors (Key Players), while Perum Perhutani and BPS play the role of strategic supporters (Subjects). Inter-stakeholder collaboration is key to strengthening the real contribution of the forestry sector to regional economic development and sustainable forest management.